2021
DOI: 10.1007/s10877-021-00660-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a single aerobic exercise on perfused boundary region and microvascular perfusion: a field study

Abstract: The endothelium and the glycocalyx play a pivotal role in regulating microvascular function and perfusion in health and critical illness. It is unknown today, whether aerobic exercise immediately affects dimensions of the endothelial surface layer (ESL) in relation to microvascular perfusion as a physiologic adaption to increased nutritional demands. This monocentric observational study was designed to determine real-time ESL and perfusion measurements of the sublingual microcirculation using sidestream dark f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Previous studies conducted in our center, have shown that PBR 5–25 values in healthy adult controls (slightly older than our participants) ranges between 1.77 and 1.78 μm [ 29 , 30 ]. Similarly, a small observational study of healthy young adults measuring PBR 5–25 before and after exercise, reported a baseline PBR 5–25 of 1.86 μm [ 31 ]. Compared to the results of PBR 5–25 at 48 ± 4 weeks (1.93 μm) in our cohort, these values show that EG integrity is not completely restored among PLWH after one year of cART.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted in our center, have shown that PBR 5–25 values in healthy adult controls (slightly older than our participants) ranges between 1.77 and 1.78 μm [ 29 , 30 ]. Similarly, a small observational study of healthy young adults measuring PBR 5–25 before and after exercise, reported a baseline PBR 5–25 of 1.86 μm [ 31 ]. Compared to the results of PBR 5–25 at 48 ± 4 weeks (1.93 μm) in our cohort, these values show that EG integrity is not completely restored among PLWH after one year of cART.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed glycocalyx-shedding by laboratory testing of shedding products (heparan sulphate and syndecan-1) into the circulation only. A complimentary method of measuring glycocalyx-shedding, visualization of the perfused boundary region in sublingual vessels by sidestream dark field microscopy could not be employed in our patients, as insertion of the camera probe would have interfered with the surgical field and might have endangered the intra-oral flap [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently employed in different clinical situations and conditions to assess the ESL [ 14–18 ]. The calculation of the PBR has previously been described in detail [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%